An Evaluation of Cots-Based Radar for Very Small Drone Sense and Avoid Application - Rashid, Nur Emileen; Mohd Shariff, Khairul Khaizi; Zainuddin, Suraya (International Journal of Integrated Engineering, 2022)
The use of very small unmanned aerial vehicles (UAVs) are increasingly common these days but its applications are limited to the pilot line-of-sight view. To extend its use beyond the pilot view, UAVs need to be equipped sense and avoid (SAA) system to avoid potential collisions. However, the development of SAA for very small drones is still in the infancy stage mainly due to the high cost of design and development for reliable range sensors. Recent developments of very small size and lightweight commercial off-the-shelf (COTS)-based radar systems may become a crucial element in very small drone applications. These types of radars are primarily developed for industrial sensing but can be adapted for applications such SAA. Thus, this paper contributes to the survey of a miniature and lightweight radar sensor to assist the SAA development. The focus of this paper is to analyse the eligibility of a COTS-based radar in detecting very small drones. For this purpose, we used a frequency-modulated continuous radar (FMCW) developed by Infineon Technologies.  Field test results show the real-time capability of the radar sensor to detect the very small drones within Â± 0.5 meters in static and dynamic conditions.